2020
DOI: 10.1097/mej.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 epidemic in the Seine-Saint-Denis Department of Greater Paris: one month and three waves for a tsunami

Abstract: Introduction Worldwide, the COVID-19 epidemic has put health systems to the test. The excess mortality is partly due to the influx of patients requiring hospitalization and intensive care. We propose that the chronology of epidemic spread gives a window of time in which hospitals can act to prevent reaching capacity. Methods The out-of-hospital SAMU Emergency Medical System in an entry point into the French health care system. We recorded the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…On the other hand risk of in-hospital mortality increased only in aged patients and was not associated with the Black race, sex, comorbidities, obesity and other factors after multivariate adjustment [2]; this phenomenon was also confirmed in other races, i.e., Asians and Hispanics, compared with the White race [3,4]. Moreover, since COVID-19 is an infectious disease that spreads mainly through the droplet route by close contact in dense human societies, metropolitan areas, such as New York City in the USA [5] and Lombardy in Italy [6], Paris in France [7], Sao Paulo in Brazil [8], and so on, have tended to be regional epicenters. However, associations between population dynamics, e.g., population size, density, migrants and urbanization and the morbidity/mortality of COVID- 19 have not yet been well examined.…”
Section: Introductionmentioning
confidence: 73%
“…On the other hand risk of in-hospital mortality increased only in aged patients and was not associated with the Black race, sex, comorbidities, obesity and other factors after multivariate adjustment [2]; this phenomenon was also confirmed in other races, i.e., Asians and Hispanics, compared with the White race [3,4]. Moreover, since COVID-19 is an infectious disease that spreads mainly through the droplet route by close contact in dense human societies, metropolitan areas, such as New York City in the USA [5] and Lombardy in Italy [6], Paris in France [7], Sao Paulo in Brazil [8], and so on, have tended to be regional epicenters. However, associations between population dynamics, e.g., population size, density, migrants and urbanization and the morbidity/mortality of COVID- 19 have not yet been well examined.…”
Section: Introductionmentioning
confidence: 73%
“…This service is based on a medical response to emergency calls where an emergency physician decides the appropriate response for each case. Depending on the evaluation of the severity of the case and the circumstances, the phone response may be a medical advice, a home visit of a GP, the dispatch of an ambulance or rescue workers, and, in the most serious cases, sending a mobile intensive care unit (MICU) staffed by an emergency physician sent on scene as a second or a first tier [13]. To cope with the surge of calls during the COVID-19 crisis, the 4 SAMUs involved in the study have increased their response capacity by creating specific procedures for COVID-19-related calls, such as staff increase, dedicated computer stations, interactive voice server, video consultation, sending instructions by SMS.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in Seine-Saint-Denis, which is a French department bordering Paris to the northeast and is a part of Greater Paris, Lapostolle et al reported that the COVID-19 pandemic increased the number of calls for the Service d'Aide Medicale Urgente (SAMU), the number of mobile intensive care unit (MICU) dispatches, and the number of emergency department visits compared to the average of the previous ve years. [20] Although the reason for the differences between their study and the present study is not clear, the SAMU in France provides several medical services that included medical advice, hospital transfer by a non-emergency transport ambulance, dispatch of a rescue vehicle or of a general practitioner to the patient's home or, in severe cases and/or when rapid prehospital care is required, a MICU, with an emergency physician, nurse, and special paramedic on board. Contrastingly, the only service provided by the EMS system in Japan is ambulance dispatch, and the differences in services provided by the SAMU in France versus the EMS system in Japan may have affected the difference in results.…”
Section: Discussionmentioning
confidence: 66%